PENERAPAN PEMBELAJARAN MATEMATIKA REALISTIK INDONESIA (PMRI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IVA SD NEGERI 032 MUMUGO KECAMATAN TANAH PUTIH - ', Roslinawati; Marhadi, Hendri; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Absract: This research is motivated by the lack of results of the fourth grade students learn math Mumugo 032 with an average grade 62,80. KKM Mathematics is 70. Among students 25 people only 10 students who achieved KKM with classical completeness 40%. This study is an action research that aims to improve learning outcomes Math Mumugo 032 Elementary School fourth grade students to the implementation of  PMRI. Formulation of the problem: if the implementation PMRI can improve learning outcomes Mathematics Fourth grade students of SD Negeri  Mumugo 032. The research was conducted on SD Negeri 032 Mumugo to 2 cycles. The subjects of this study were fourth grade students totaling 25 people who used the data source. Data collection instruments in this thesis is the student activity sheets and teachers as well as learning outcomes. This thesis presents the results obtained from the study of daily test values before treatment with an average of 62,80 increase in cycle 1 to 72,00 in both categories. In cycle 2 increased by an average of 78,80 with a very good category. Activities of teachers in the learning process in cycle 1 72.50% with both categories. While on cycle 2 91,20% with very good category. Mastery learning students also have improved much. Before the measures, students who completed only 10 people (40%) with an average value of 62,80. After the measures in cycle 1 students who pass to 19 people (76.00%) with a mean of rat 72,00. The cycle 2 of students who pass the increase to 22 people (88.00%) with a mean of rat 78,80 so that the total increase of 12 persons (48,00%). The implementation PMRI can improve learning outcomes Elementary School fourth grade math students Mumugo 032. Key Words:       Learning Mathematics Indonesian Realistic (PMRI), Mathematics Learning Outcomes, stundents of SD